Inter-institutional agreement for the academic year 2010/2011 LLP-Erasmus Programme between Universidade Lusíada de Lisboa and Università degli Studi di Torino - Universidade Lusíada de Lisboa (2016)
- Cooperate in the Erasmus activities. - Subject area: Political science.